The Managing Director's Global Policy Agenda, Annual Meetings 2020 : Catalyzing a Resilient Recovery. (Policy Papers; Policy Paper, 2020)
The global economic outlook is improving, but the recovery is partial, uneven, and uncertain. Policies must restore confidence, support jobs, and boost growth. Now is the time to also build a more resilient future. We must work together to support the most vulnerable countries and people.